Thankful for the maverick - Alers, Rochelle (Harlequin special edition, 2022)
As a rodeo champion, Brynn Hawkins is always on the road, but something about older, gruff-but-sexy rancher Garrett Abernathy makes her think about putting down roots. Brynn doesn't know why she is so drawn to a man who says he doesn't date, but his quiet dignity makes her rethink everything. As Thanksgiving approaches, Brynn fears she's running out of time, but she's determined to find her way into this callused cowboy's heart.